From Tradition to Modernity: Unraveling the Multifaceted Cultural Narratives and Anthropological Perspectives of Ghanaian Society in a Globalized World - William, Daitey; Nathalie, Bonnah (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2025)
This study examines the intricate cultural narratives and anthropological perspectives of Ghanaian society as it navigates the waters of globalization. Ghana, with its rich tapestry of ethnic groups, languages, and traditions, presents an ideal context to explore the tension between tradition and modernity. This research delves into key anthropological concepts, such as kinship systems, ritual practices, and identity formation, using qualitative methodologies including interviews and participant observation. Findings reveal that while globalization exerts significant influence, many Ghanaians actively engage with their cultural heritage, balancing modernization with traditional values. This study contributes to the broader anthropological discourse on cultural adaptation and preservation, highlighting the role of community resilience in maintaining identity amidst changing socio-economic landscapes. The implications of these findings underscore the need for ongoing research into how Ghanaian society can continue to bridge the gap between its historical roots and contemporary realities.